Relaxation and crystallization studied by observing the surface morphology evolution of atomically flat Pt57.5Cu14.7Ni5.3P22.5 upon annealing. (June 2020) - Chen, Zheng; Datye, Amit; Ketkaew, Jittisa; Sohn, Sungwoo; Zhou, Chao; Dagdeviren, Omur E.; Schroers, Jan; Schwarz, Udo D.
Abstract: The evolution of the surface morphology of Pt57.5 Cu14.7 Ni5.3 P22.5 bulk metallic glasses thermoplastically formed by replication of SrTiO3 single crystals during heat treatments is investigated by atomic force microscopy. Due to the unique imprinting process, the surface of the bulk metallic glass features a terraced structure with sub-angstrom surface roughness. Upon heating over the material's glass transition temperature, the surface rearranges and relaxes towards a more stable, denser packed glass by smoothening out steps and increasing on-terrace surface roughness. With further increasing annealing temperatures, substantial surface alterations are observed because of increased arrangement kinetics and the onset of crystallization. Graphical abstract: Image, graphical abstract